Immune scores in colorectal cancer: Where are we?. (November 2020) - Malka, David; Lièvre, Astrid; André, Thierry; Taïeb, Julien; Ducreux, Michel; Bibeau, Frédéric
Abstract: There is growing evidence that the immune system may prevent the occurrence, growth and metastatic diffusion of colorectal cancer (CRC). The role played by the adaptive immune response at the tumour site is critical in the balance between tumour invasion and defence against cancer. Recent data have shown that the evaluation of this immune response may help to define the prognosis and possibly the treatment of localised CRC as well as metastatic CRC. Tumour infiltrates with T cells (CD3+), cytotoxic T cells (CD8+) and memory T cells (CD45RO+) are the immune parameters most consistently and strongly associated with good clinical outcome in CRC. Several scoring systems have been developed, including the Immunoscore®, based on the immunohistochemical determination with a digital image analysis system of the density of CD3+ and CD8+ lymphocytes in the centre and the invasive margin of the tumour. This review will focus on the different immunoscoring systems developed in CRC, their performance, their limitations and their potential for improving patients' care in the future. Highlights: The immune system helps preventing the occurrence, growth and diffusion of CRC. Different scoring systems evaluating lymphocyte infiltrates in CRC have been developed. The Immunoscore® system relies on immunohistochemistry and image analysis. Its prognostic performance has been shown in primary and metastatic CRC. Its predictive performance needs more prospective data.